Results of monitoring of reintroduced populations of Calophaca wolgarica in the Saratov region - Efimenko, Savelii F.; Parhomenko, Alena Sergeevna; Shilova, Irina V.; Grebenyuk, Lyudmila V.; Kuliseva, Yulia I.; Kashin, Alexandr Stepanovich (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология)
For 11 years, the staff of the Scientifi c Research Center “Botanical Garden” of SSU named after N.G. Chernyshevsky have been reintroducing a rare protected plant, Calophaca wolgarica (L. fi l.) DC., into potentially suitable places in the Saratov Region. This species is considered extinct in the region. Restoration of the species in the Saratov Region will expand its range, increase the biodiversity of the local fl ora and enrich biogeocenoses. Seed material for the reintroduction of C. wolgarica was collected from natural cenopopulations in the Volgograd Region. In 2013–2015 the seeds were sown in Voskresensky (near the village of Ershovka) and Krasnoarmeysky (the villages of Kamenka, Mordovo, Rogatkino, Belogorskoye) districts of the Saratov right bank, in Perelyubsky (the village of Kutseba), Pugachevsky (near the village of Maksyutovo), Fyodorovsky (the village of Dolina) districts of the left bank. In 2020, sowing was carried out in Pugachevsky (the villages of Maksyutovo, Solyanka) and Yershovsky (the village of Novorozhenka) districts. Seedlings were planted in Krasnoarmeysky district (the villages of Rogatkino, Kamenka), but they died in the year of planting. The seeds germinated in Pugachevsky, Fyodorovsky, Yershovsky and Krasnoarmeysky districts. To analyze the results of C. wolgarica reintroduction in the Saratov region, the dynamics of the number of individuals, their ontogenetic and vitality structure were assessed in the created populations. The vitality structure was analyzed for individuals whose ontogenetic state was predominant in terms of numbers for a specifi c year of observations. According to the results of the studies conducted in the period from 2016 to 2024, out of six districts selected as sites for the reintroduction of C. wolgarica, three – Pugachevskiy, Fyodorovsky and Yershovsky – are suitable for the growth of this species, and reintroduction is promising here. In two reintroduction populations from Pugachevskiy and Fyodorovsky districts, some of the plants have reached the generative period. These populations are potentially capable of self-sustaining. The most favorable habitats for C. wolgarica are located in the Pugachevskiy district.